2007
DOI: 10.1007/s11240-007-9314-4
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of node and lateral shoot formation in micropropagation of olive (Olea europaea L.) by using dikegulac

Abstract: Dikegulac, a growth regulator, was shown to stimulate in vitro shoot multiplication of olive cultivars Canino, Frantoio, Moraiolo, but not cultivars Rosciola and Piantone di Moiano. The Rugini Olive Medium including zeatin (4.5 lM) was used supplemented with a range of dikegulac concentrations (0-133.4 lM). An optimal result in number of shoots and nodes was obtained on cultivars Canino, Frantoio and Moraiolo at 66.7 lM dikegulac. Higher concentrations did not stimulate additional shoot and node formation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 20 publications
2
16
0
5
Order By: Relevance
“…Spreng. Similar explanation was proposed in olives, where 66.7 and 100.5 μM DS in the cultivars Canino and Moraiolo and 33.8-100.5 μM in Frantoio cultivar increased the number of shoots/explant (Mendoza de Gyves et al, 2008). On the other hand, a reduced number of shoots was reported for the in vitro culture of Vaccinium corymbosum L. cv 'Herbert' when DS combined with 5 mg/l 2-isopentenyladenine (2ip) (Litwińczuk and Prokop, 2010 In Sideritis raeseri L., DS regardless its concentration (10-1500 μM) did not influence shoot length in a considerable degree (12.48-16.11 mm) (Table 1).…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…Spreng. Similar explanation was proposed in olives, where 66.7 and 100.5 μM DS in the cultivars Canino and Moraiolo and 33.8-100.5 μM in Frantoio cultivar increased the number of shoots/explant (Mendoza de Gyves et al, 2008). On the other hand, a reduced number of shoots was reported for the in vitro culture of Vaccinium corymbosum L. cv 'Herbert' when DS combined with 5 mg/l 2-isopentenyladenine (2ip) (Litwińczuk and Prokop, 2010 In Sideritis raeseri L., DS regardless its concentration (10-1500 μM) did not influence shoot length in a considerable degree (12.48-16.11 mm) (Table 1).…”
Section: Resultssupporting
confidence: 73%
“…In a previous study conducted by Sarropoulou et al (2014) in the cherry rootstock CAB-6P (Prunus cerasus L.), DS when applied at 120 μM or 150 μM concentrations diminished shoot length considerably. In addition, Mendoza de Gyves et al (2008) reported that DS (100.5 and 133.4 μM) had a negative effect on shoot length in the olive cultivars Canino, Frantoio and Moraiolo. According to Thetford and Berry (2000), DS exerted an inhibitory effect on height in euonymus, forsythia, Chinese privet, waxleaf privet and azalea.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such failure is mainly due to the different behavior of the various cultivars, which requires setting up a specific protocol for each variety (Bahrami et al, 2010;Lambardi and Rugini, 2003;Rostami and Shahsavar, 2012), and the use of zeatin, which is very expensive (Mendozade Gyves et al, 2008). To solve or reduce these problems, efforts have been made to identify alternative cytokinins or compounds/ protocols able to improve the regeneration efficiency of the explants to reduce the unit cost of regenerated shoots (Ali et al, 2009;Mendoza-de Gyves et al, 2008).…”
mentioning
confidence: 99%